Subjective Well-Being Pada Siswa Smp Yang Membolos Di Surakarta - Prasetyo, Anggoro Hadhi, Rini Lestari, S.Psi, M.Si (2017)
Subjective well-being is the cognitive and emotional evaluation of individuals to life, as understood by the layman as happiness, serenity, and life satisfaction. School truant behavior more common in male student and female student. This study aims to understand and describe the condition of subjective well-being in junior high school students who play truant. This study was conducted in one of the private junior high school in the city of Surakarta. Subject or informants in this study of 6 (six) junior high school students who play truant. This study used a descriptive approach qualitative with phenomenological research model, data collection using semi-structured interview (semistructured interview) and descriptive observations. Data analysis techniques used in this study is the interactive data analysis techniques that consist of four (4) phases of data collection, data reduction, data display, and conclusion. The results of this study indicate that women are more often truant students than male students. They are not satisfied with those felt they currently are bored, sad, and have yet to find something that can make a happy and one of them felt sorry for ditching school. The subject also has a good relationship with parents and teachers, they feel uncomfortable while in school because it is not like a friend at school, not doing homework and feel tired for school. Therefore, the subject can not refuse an invitation from a friend to play truant because they make skipping school as a way to resolve the problems experienced. Factors that may affect the subjective well-being in students who play truant are social relationships, personality factors, factors optimism and gratitude, experience, and confidence in ourselves